Rigid peptide scaffold-incorporated structural analogs of the potent antidepressant peptide drug rapastinel (GLYX-13) - Nadimpally, Krishna Chaitanya; Chakrapani, Aswathi; Prabhu, Priyanka J.; Madica, Krishnaprasad; Sanjayan, Gangadhar J. (Chemistryselect, 2017)
Rapastinel (GLYX-13) is a natural amidated tetrapeptide (Thr-Pro-Pro-Thr-NH2)endowed with strong antidepressant property. Rapastinel shows considerable promise for treating drug-resistant major depressive disorder (MDD), and is under clinical phase III development. Herein, we report the synthesis of a novel class of analogues of the potent antidepressant peptide drug rapastinel featuring rigid dipeptide scaffolds comprising proline (L/D) and amino thiophene carboxylates (Atc). Amino thiophene carboxylate is a conformationally constrained aromatic beta-amino acid, known to rigidify peptide backbones thereby limiting the conformational flexibility of peptides and improving proteolytic stability.